Adult Intramedullary Ewing Sarcoma of the Proximal Hip. (12th June 2014) - Gongidi, Preetam; Jasti, Siva; Rafferty, William; Barshay, Veniamin; Lackman, Richard
Abstract : Ewing sarcoma of bone is classically a permeative lesion in the diaphysis of long bones in children. While they occur primarily in children and adolescents, they can be seen in young adults in their 20s, but these are typically seen in flat bones. The permeative nature of the lesion can elicit new bone formation creating a partially sclerotic appearance, cortical expansion presenting as a "Codman triangle, " or have an "onion-skin" type of aggressive periosteal reaction/periostitis. Ewing sarcoma is rarely seen without an associated soft-tissue mass and is even rarer to just have benign-appearing periostitis (e.g., thick, uniform, or wavy cortex). We present such a case of Ewing sarcoma in a young adult confined to just the medullary metadiaphysis without cortical erosion or soft-tissue mass. To the best of our knowledge, this is the first case to be reported in the radiology literature.